Consensus Statements on Driving for Persons with Dementia. Issue 2 (3rd April 2014) - Wheatley, Carol J.; Carr, David B.; Marottoli, Richard A.
ABSTRACT: The presence of dementia can have a profound effect on a person's capacity for driving, and will lead to eventual cessation of driving and reliance on alternative transportation options. This paper offers evidence and discussion that affirm eight consensus statements related to drivers with dementia and the impact of dementia on the driving task. These statements offer guidance for occupational therapy practitioners when addressing driving and community mobility, a valued instrumental task of daily living.